Effects of shading and composition on green roof media temperature and moisture. (1st March 2021) - Bollman, Michael A.; DeSantis, Grace E.; Waschmann, Ronald S.; Mayer, Paul M.
Abstract: Three of the primary functions of green roofs in urban areas are to delay rainwater runoff, moderate building temperatures, and ameliorate the urban heat island (UHI) effect. A major impediment to the survival of plants on an unirrigated extensive green roof (EGR) is the harsh rooftop environment, including high temperatures and limited water during dry periods. Factors that influence EGR thermal and hydrologic performance include the albedo (reflectivity) of the roof and the composition of the green roof substrate (growing media). In this study we used white, reflective shading structures and three different media formulations to evaluate EGR thermal and hydrologic performance in the Pacific Northwest, USA. Shading significantly reduced daytime mean and maximum EGR media temperatures and significantly increased nighttime mean and minimum temperatures, which may provide energy benefits to buildings. Mean media moisture was greater in shaded trays than in exposed (unshaded) trays but differences were not statistically significant. Warmer nighttime media temperatures and lack of dew formation in shaded trays may have partially compensated for greater daytime evaporation from exposed trays. Media composition did not significantly influence media temperature or moisture. Results of this study suggest that adding shade structures to green roofs will combine thermal, hydrologic, and ecological benefits, and help achieve temperature and light regimes that allow for greater plant diversity on EGRs. Highlights: Reflective shading structures combine the benefits of cool roofs and green roofs. Shading reduced green roof temperatures during the day and increased them at night. Shading did not significantly alter green roof moisture dynamics. Lack of dew formation in shaded trays may have offset reduced daytime evaporation. Green roof media composition did not influence effects of shading.